2004
DOI: 10.1104/pp.104.038703
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Transfer-Reaction Mass Spectrometry as a New Tool for Real Time Analysis of Root-Secreted Volatile Organic Compounds in Arabidopsis

Abstract: Plant roots release about 5% to 20% of all photosynthetically-fixed carbon, and as a result create a carbon-rich environment for numerous rhizosphere organisms, including plant pathogens and symbiotic microbes. Although some characterization of root exudates has been achieved, especially of secondary metabolites and proteins, much less is known about volatile organic compounds (VOCs) released by roots. In this communication, we describe a novel approach to exploring these rhizosphere VOCs and their induction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(141 citation statements)
references
References 50 publications
4
131
0
6
Order By: Relevance
“…For example, one molecule of ethanol contains two C atoms, leaving two possible positions for the integration of a 13 C isotope, giving a total chance of 2.2% for an incorporation of 13 C. The remaining 0.1% may result from the incorporation of 2 H (6×0.0115%) and 17 O (1×0.038%). Previous investigations showed that compounds derived from molecular fragmentation contributed to masses 41, 43 and 69 in high concentrations (Mayr et al 2003;Yeretzian et al 2003;Ezra et al 2004;Steeghs et al 2004;Mayrhofer et al 2006;Araghipour et al 2008). In this investigation, these masses were also found in considerable amounts.…”
Section: Detection and Identification Of Vocsupporting
confidence: 58%
“…For example, one molecule of ethanol contains two C atoms, leaving two possible positions for the integration of a 13 C isotope, giving a total chance of 2.2% for an incorporation of 13 C. The remaining 0.1% may result from the incorporation of 2 H (6×0.0115%) and 17 O (1×0.038%). Previous investigations showed that compounds derived from molecular fragmentation contributed to masses 41, 43 and 69 in high concentrations (Mayr et al 2003;Yeretzian et al 2003;Ezra et al 2004;Steeghs et al 2004;Mayrhofer et al 2006;Araghipour et al 2008). In this investigation, these masses were also found in considerable amounts.…”
Section: Detection and Identification Of Vocsupporting
confidence: 58%
“…The mean seasonal diurnal behavior of acetonitrile suggests it may be used as a conservative tracer of boundary layer dynamics in interpreting the mean seasonal diurnal curves for the other species reported here. Isoprene is mainly emitted by chloroplasts as a function of light and temperature (Steeghs et al, 2004). Hence, isoprene emissions occur in the daytime and stop at night with summertime emissions exceeding those in winter.…”
Section: Biomass Burning Tracer -Acetonitrile (Ch 3 Cn M/z 42)mentioning
confidence: 99%
“…However, volatiles also act as direct repellents or toxicants for herbivores and pathogens, and some have the potential to eliminate reactive oxygen species. This also includes root-emitted volatiles, which may function as antimicrobial or anti-herbivore substances or exhibit allelopathic activities that increase the ecological competitiveness of the plant (Steeghs et al, 2004). Accordingly, plant volatiles can minimize the growth suppression of epiphytic bacteria by the phytopathogenic fungus Botrytis cinerea and thus affect population dynamics on leaf surfaces (Abanda- Nkpwatt et al, 2006a), while simple alcohols emitted by leaves may provide a carbon and energy source for epiphytic methylotrophs (Abanda-Nkpwatt et al, 2006b).…”
Section: Biological Functions Of Plant Volatilesmentioning
confidence: 99%